Alteration of Ribosomal Protein S4 by Mutation Linked to Kasugamycin-Resistance in Escherichia coli - Zimmermann, Robert A. (1973)
An alteration in the chromatographic mobility of 30S ribosomal protein S4 from two kasugamycin-resistant (ksgA) strains of E. coli was observed. The locus determining this alteration frequently cotransduced with ksgA but could be separated from it by transduction and conjugation. Since the structural gene for protein S4 is thought to lie some 30 min from ksgA on the E. coli chromosome, the product of the newly-identified gene may modify protein S4. We propose to designate this gene ramB. Reconstitution of 30S subunits from RNA and protein components of ksgA ramB and ksgA(+)ramB(+) strains demonstrated that ribosomal resistance to kasugamycin was due to altered 16S RNA and not to altered protein S4. The altered 16S RNA was undermethylated, and a methylating enzyme that acts on 16S RNA from ksgA strains was present in ksgA(+) but not in ksgA strains.